Does percutaneous tibial nerve stimulation improve global pelvic function in women with faecal incontinence?. (May 2016) - Kelly, S. L.; Radley, S. C.; Brown, S. R.
Abstract: Aim: Percutaneous tibial nerve stimulation (PTNS) is a minimally invasive treatment for faecal incontinence. Many patients with faecal incontinence have coexisting pelvic floor disorders such as urinary incontinence and vaginal symptoms. We utilized a pelvic floor assessment tool to analyse any effect of PTNS on global pelvic floor function. Methods: Patients with faecal incontinence attending our institution who had failed to respond sufficiently to biofeedback were offered a course of PTNS. Patients underwent pre‐ and post‐stimulation assessment with a validated electronic Personal Assessment Questionnaire – Pelvic Floor (ePAQ‐PF) for pelvic floor disorders. Scores were compared to assess the effect of treatment on global pelvic floor function. Results: During the study period pre‐ and post‐stimulation ePAQ‐PF data were available for 60 patients (55% of all patients starting PTNS). In this cohort there was a significant improvement in bowel continence, bowel related quality of life, irritable bowel syndrome and bowel evacuation with a large effect size for continence and bowel related quality of life. There was also a significant improvement in non‐bowel related symptoms, including urinary pain and stress incontinence, urinary related quality of life and bowel related sexual function. Sixty‐five per cent of those who answered the question reported improvement in global health after stimulation. Conclusion: For patients presenting with faecal incontinence, PTNS appears to have a positive effect on bowel related function in approximately two‐thirds of patients. However, for treatment responders, improvement appears to relate mainly to improvement in bowel related function rather than a global pelvic floor effect.